ChemInform Abstract: Synthesis of Enantiopure 3‐Hydroxypiperidines from Sulfinyl Dienyl Amines by Diastereoselective Intramolecular Cyclization and [2, 3]‐Sigmatropic Rearrangement. Issue 51 (December 2015) - Simal, Carmen; Bates, Robert H.; Urena, Mercedes; Gimenez, Irene; Koutsou, Christina; Infantes, Lourdes; Fernandez de la Pradilla, Roberto; Viso, Alma
Abstract: A wide range of tetrahydropyridin‐3‐ols is prepared by a general protocol starting from stereodefined 4‐sulfinyl dienyl amine derivatives.